2020
DOI: 10.3389/fpls.2020.583584
|View full text |Cite
|
Sign up to set email alerts
|

HaCRT1 of Heterodera avenae Is Required for the Pathogenicity of the Cereal Cyst Nematode

Abstract: Cereal cyst nematodes are sedentary biotrophic endoparasites that secrete effector proteins into plant tissues to transit normal cells into specialized feeding sites and suppress plant defenses. To understand the function of nematode effectors in Heterodera avenae, here, we identified a calreticulin protein HaCRT1, which could suppress the cell death induced by Bax when expressed in Nicotiana benthamiana. HaCRT1 is synthetized in the subventral gland cells of pre-parasitic second-stage nematodes. Real-time PCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…The Calr of the root-knot nematode Meloidogyne incognita suppresses PAMP-triggered immunity (PTI) whilst infecting its host (116); PTI can be considered the innate immune response of plants. A similar effect was encountered when studying the function of Heterodera avenae Calr (HaCalr) (117); the same study showed that treatment of plants with HaCalr reduced the intensity of the respiratory burst and facilitated H. avenae parasitism in early stages. Insects fall victim to parasitism as well: an important immunoprotective mechanism against parasites is the encapsulation of the invading organism, a process that requires hemocyte spreading to occur.…”
Section: Immunomodulatory Effects Of Parasite Calreticulinmentioning
confidence: 56%
“…The Calr of the root-knot nematode Meloidogyne incognita suppresses PAMP-triggered immunity (PTI) whilst infecting its host (116); PTI can be considered the innate immune response of plants. A similar effect was encountered when studying the function of Heterodera avenae Calr (HaCalr) (117); the same study showed that treatment of plants with HaCalr reduced the intensity of the respiratory burst and facilitated H. avenae parasitism in early stages. Insects fall victim to parasitism as well: an important immunoprotective mechanism against parasites is the encapsulation of the invading organism, a process that requires hemocyte spreading to occur.…”
Section: Immunomodulatory Effects Of Parasite Calreticulinmentioning
confidence: 56%
“…Meanwhile, OsCML31 and OsHMGB1 were fused with nYFP though cloning to pSPYNER173 vectors (Waadt et al, 2008). The A. tumefaciens strain EHA105 containing those recombined constructs were cultured and infiltrated into the leaves of N. benthamiana as previously described (Liu et al, 2020). ER‐GFP(CD3‐955) and ER‐RFP(CD3‐959) were used as endoplasmic reticulum markers (Nelson et al, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…The constructs pYBA‐1143: MgCRT1 and pYBA‐1132: OsCML31 were transformed into A. tumefaciens EHA105 and co‐expressed in N. benthamiana leaves as previously described (Liu et al, 2020). Two days after infiltration, total protein was extracted with native extraction buffer (50 mM tris‐HCl at pH 6.8, 4.5% SDS, 7.5% β‐m2‐mercaptoethanol, 9 M urea, and protease inhibitor cocktail).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations